2018
DOI: 10.5194/aab-61-245-2018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the addition of wet brewers grain to the diet of lambs on body weight gain, slaughter valueand meat quality

Abstract: Abstract. Wet brewers grain (WBG) is successfully used in animal nutrition, and due to its high fiber content, especially in ruminants. The low cost of this fodder also has an impact on the economic of production. The aim of this study was to determine the effects of adding WBG to lamb fodder on the body weight gain, slaughter value and meat quality. The experiment was conducted on 40 male lambs of Polish Lowland sheep. The lambs were divided into two feeding groups, the control and the experimental (20 heads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Similar ADG recorded in this study was mainly due to the similar nutrient intakes among treatments. Similar results also reported that feeding lambs containing brewer residue did not affect body weight gain (Radzik-Rant et al, 2018, 2019. By contrast, results from other studies suggested that dried brewer inclusion increased daily gain in cattle (Keopaseuth et al, 2017).…”
Section: Digestibility and Growth Performancesupporting
confidence: 78%
“…Similar ADG recorded in this study was mainly due to the similar nutrient intakes among treatments. Similar results also reported that feeding lambs containing brewer residue did not affect body weight gain (Radzik-Rant et al, 2018, 2019. By contrast, results from other studies suggested that dried brewer inclusion increased daily gain in cattle (Keopaseuth et al, 2017).…”
Section: Digestibility and Growth Performancesupporting
confidence: 78%
“…22 The CP content of WBGB noted in this study was similar to 19.8% and 19.45% earlier reported 19,27 respectively. Higher (25.05%, 25.5%) 25,28 respectively and lower CP values (<20%) of WBGB were also reported. 29 The NDF and ADF contents of WBGB of the present study was relatively similar (47.1% and 28.4%) to those earlier reported 19,30 respectively; however lower NDF and ADF values as well were reported.…”
Section: Resultsmentioning
confidence: 84%
“…One of the most prominent plant by-products arise mainly from oilseed mills and brewing industries [2]; called dried brewer's grains (DBG). The latter could be an appropriate low-cost replacer for traditional feedstuffs (e.g., corn and soybean meal), as it contains a fair amount of feed residues following the brewing process [3][4][5][6]. It consists of around 20% crude protein, 6% ether extract, 15% crude fiber and 4% ash, in addition it has an adequate amount of essential AA (0.4% methionine, 0.9% lysine, 1.2% phenylalanine, 0.4% tryptophan, 1.1% threonine and 1.6% valine) [7].…”
Section: Introductionmentioning
confidence: 99%